Polyacrylate binder and application thereof, electrode plate and lithium ion battery
By limiting the content of cyano, ester and carboxylate in polyacrylate binders, the problems of insufficient bonding strength, high cost and unfriendly environment of PVDF binders are solved, and the safety performance of lithium-ion batteries is achieved and cycle performance is improved and environmentally friendly.
Patent Information
- Application Number
- CN202411454068.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The polyvinylidene difluoride (PVDF) adhesive used in existing lithium-ion batteries has problems such as insufficient adhesion, high cost, limited source and unfriendly environment, which affects the safety and circulation performance of the battery.
A polyacrylate binder is proposed to achieve good bonding properties by defining cyano (-CN), ester group (-COOR2) and carboxylate (-COOR1) in the binder molecular chain, and Use water as a solvent to avoid the use of harmful organic solvents, reduce costs and improve environmental friendliness.
The polyacrylate adhesive provides excellent bonding performance, improves the safety performance, cycle performance, rate performance and high and low temperature discharge performance of the battery, and is environmentally friendly, has low cost, and is suitable for industrial production.
Smart Images

Figure CN119161834A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary battery materials, and in particular to a polyacrylate binder and application thereof, an electrode sheet and a lithium ion battery. Background Art
[0002] Lithium-ion batteries are widely used in 3C, electric vehicles, power tools and other products due to their high energy density, no memory effect, long cycle life, environmental friendliness, and adaptability to various environments. In practical applications, in order to improve the safety performance of batteries, introducing safety coatings into the battery pole pieces is one of the commonly used measures in the industry.
[0003] In the related art, most safety coatings contain a certain proportion of inorganic fillers, conductive agents and binders. Currently, the commonly used binder is mainly polyvinylidene fluoride (PVDF). However, PVDF binders have the following shortcomings: (1) Performance: The bonding force provided by PVDF mainly depends on the van der Waals force between molecules, which leads to the problem of insufficient bonding force of safety coatings using PVDF; (2) Price and source: Currently, high-performance PVDF is expensive and its source is limited, which greatly increases the manufacturing cost of electrode sheets; (3) Environmental friendliness: When using PVDF, highly volatile organic solvents such as NMP (N-methylpyrrolidone) are required, which not only pollutes the environment, but also is harmful to human health. At the same time, the use of NMP further increases the material cost and the corresponding recycling and processing cost.
[0004] Therefore, it is of great significance to solve the problems of insufficient bonding strength, high cost, limited source and environmental unfriendliness of current binders, and to provide binders with good bonding performance, green and safe, cost advantages, environmental friendliness and the ability to effectively improve battery safety and cycle performance. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes a polyacrylate binder and its application, an electrode sheet and a lithium-ion battery, aiming to solve the problems of insufficient bonding force, high cost, limited source and environmental unfriendliness of the current binder.
[0006] In a first aspect of the present invention, a polyacrylate adhesive is provided, wherein the structural formula of the polyacrylate adhesive is: ; Among them, R 1 Each occurrence is independently selected from H, Li or Na; R 2 Each occurrence is independently selected from substituted or unsubstituted C 1 ~C10 The alkyl group; And 5≤(x+z) / y≤20, 1.2≤z / x≤2, x, y, z are all not 0.
[0007] The polyacrylate adhesive according to the embodiment of the present invention has at least the following beneficial effects: the polyacrylate adhesive provided by the present invention is obtained by modifying the cyano group (-CN) and the ester group (-COOR 2 ) and carboxylates (-COOR 1 ) content is limited, so as to achieve good bonding performance; and the binder is water-soluble, the solvent is water, no harmful organic solvents such as NMP are needed, it is harmless to the human body and environmentally friendly; it is abundant in source, cheap, and can be widely used in industrial production. The above-mentioned binder is introduced into the electrode sheet as the raw material of the water-based safety coating. Based on its excellent bonding performance, the water-based safety coating can be firmly adhered to the collector surface of the electrode sheet, which can not only reduce the surface contact resistance, but also reduce the generation of collector burrs during safety testing of the battery cell, and reduce the contact short circuit between the collector burrs and the active substances in the unstable charging state, thereby improving the safety of the battery cell. In addition, by limiting the molecular weight of the binder and the content of cyano, ester and carboxylate groups in the molecular chain, the absorption rate of the binder electrolyte can be adjusted, which can significantly improve the rate performance and high and low temperature discharge performance of the battery cell, and improve the safety performance and cycle performance of the battery.
[0008] The binder provided by the present invention has a molecular chain containing a cyano group (-CN, the number of which accounts for n 1 , n 1 =z / (x+y+z))、carboxylate(-COOR 1 , R 1 Each occurrence is independently selected from H, Li, and Na, and its number accounts for n in all side chain groups 2 , n 2 =x / (x+y+z)) and ester groups (-COOR 2 , R 2 Each occurrence is independently selected from substituted or unsubstituted C 1 ~C 10 The number of alkyl groups in all side chain groups accounts for n 3 , n 3 =y / (x+y+z)), n 1 +n 2 +n 3 =1.
[0009] Among them, -CN is a strongly polar group with good electrolyte affinity and electrochemical stability, and can provide greater adhesion. However, this group is very rigid and cannot cope with the huge volume changes that occur when lithium ions are embedded in / out of the active material.
[0010] Among them, -COOR 1 They carry negative charges and repel each other, which helps the stretching of the binder molecules and promotes the uniform dispersion of the conductive agent. At the same time, they can also regulate the swelling degree of the binder in the electrolyte solvent, reduce the erosion of the adhesive by the electrolyte dissolution, and better maintain the bonding ability and bonding effect.
[0011] Among them, -COOR 2 The polarity and solubility parameters are close to those of carbonate solvents in the electrolyte, which is conducive to the binder's moderate absorption of the electrolyte. The absorption of the electrolyte will plasticize the binder, making it elastic and flexible to adapt to the periodic volume changes of the electrode active material during the charging and discharging process as lithium ions are inserted and extracted. At the same time, the absorption of the electrolyte will also increase the ionic conductivity of the water-based safety coating and promote the improvement of the low-temperature discharge performance of the battery cell.
[0012] Binders are an essential part for maintaining the integrity of the electrode, and are very important for improving the battery's specific capacity, cycle stability and other performance. Polyacrylic acid is used as a binder for the positive and negative electrodes of lithium batteries because it contains more polar functional groups, is soluble in water and has good adhesion. However, the polar groups of polyacrylic acid cause the hydrogen bonds formed between the molecular chains to result in a large chain rigidity, which is not conducive to maintaining the integrity of the electrode during the charge and discharge process. Therefore, it is imperative to control the number of polyacrylic acid functional groups, change the type of functional groups and the structure of the polyacrylic acid molecular chain in order to improve the electrical performance of lithium batteries. The present invention limits the content of cyano, ester and carboxylate groups in the binder molecular chain: (1) 1.2≤z / x≤2, that is, n 1 、n 2 Satisfy 1.2≤n 1 / n 2 ≤2; when n 1 / n 2 <1.2, it is easy to cause insufficient bonding strength of the adhesive; and when n 1 / n 2 >2, the molecular chain is in a curled state, which is not conducive to the dispersion of the conductive agent, and the binder is more susceptible to the swelling of the electrolyte; (2) 5≤(x+z) / y≤20, that is, n 1 、n 2 、n 3 Satisfy 5≤(n 1 +n 2 ) / n 3 ≤20; when (n 1 +n 2 ) / n 3When <5, the binder contains excessive -COOR 2 At this time, the binder easily absorbs excess electrolyte, the bonding force decreases rapidly, the elasticity deteriorates, and the performance of the battery cell deteriorates; when (n 1 +n 2 ) / n 3 >20, -COOR in the binder 2 If the content is too low, the elasticity of the binder is insufficient, the ionic conductivity of the water-based safety coating is low, and the low-temperature discharge performance and rate discharge performance of the battery cell are significantly reduced. Finally, the present invention achieves good bonding strength of the binder by regulating the content of cyano, ester and carboxylate groups in the binder molecular chain, and adjusts the electrolyte absorption rate of the binder, thereby improving the rate and high and low temperature discharge performance of the battery cell.
[0013] In some embodiments of the present invention, R 2 Each occurrence is independently selected from C 1 ~C 10 A straight chain alkyl, branched chain alkyl or cycloalkyl group, preferably C 1 ~C 10 A straight chain alkyl group, more preferably C 1 ~C 4 of alkyl.
[0014] In some embodiments of the present invention, the weight average molecular weight M of the polyacrylate binder is w The range is 200000~500000, for example, it can be 200000, 250000, 300000, 350000, 400000, 450000, and 500000.
[0015] In some embodiments of the present invention, the number average molecular weight M of the polyacrylate binder is n The range is 100000~400000, for example, it can be 100000, 150000, 200000, 250000, 300000, 350000, and 400000.
[0016] In some embodiments of the present invention, the weight average molecular weight M of the polyacrylate binder is w and number average molecular weight M n The ratio satisfies M w / M n ≤3, preferably M w / M n The range is 1.5~1.9.
[0017] If the molecular weight of the binder is too low, not only will the bonding force be too low, but it will also lead to an increase in the amount of binder used; if the molecular weight is too high, the viscosity will be too high and processing will be difficult. w / M n >3. The molecular weight distribution of the binder is too dispersed, which deteriorates the performance of the water-based safety coating.
[0018] In some embodiments of the present invention, the electrolyte absorption rate c of the polyacrylate binder at 80° C. is 10% to 50%, for example, 10% to 20%, 20% to 30%, 30% to 40%, or 40% to 50%.
[0019] The present invention achieves the adjustment of the electrolyte absorption rate of the binder by limiting the content of cyano, ester and carboxylate groups in the binder molecular chain. The electrolyte absorption rate c of the binder at 80°C satisfies 10%≤c≤50%. When c<10%, the binder absorbs insufficient electrolyte, has poor elasticity, and cannot buffer the periodic volume changes caused by the insertion and extraction of lithium ions from the active material. In addition, the ionic conductivity of the water-based safety coating is low, and the low-temperature discharge performance and rate discharge performance of the battery cell deteriorate. When c>50%, the binder absorbs excessive electrolyte, the water-based safety coating expands, the bonding force decreases, and the internal resistance increases, which also leads to the deterioration of the battery cell performance.
[0020] The polyacrylate binder can be prepared by conventional preparation methods in the art, for example, by any one of emulsion polymerization, solution polymerization, bulk polymerization and suspension polymerization.
[0021] In a specific embodiment, the present invention also provides a method for preparing the above-mentioned polyacrylate adhesive, comprising the steps of: S1. Adding a dispersion medium into a reaction vessel and deoxygenating the vessel; S2, according to the ratio of x, y, z, add a certain amount of acrylonitrile to the reaction vessel to provide -COOR 1 Monomer A, providing -COOR 2 Monomer B; S3, adding initiator and heating to initiate reaction; S4. After the reaction is completed, the product is filtered, dried, crushed and sieved to obtain a polyacrylate adhesive.
[0022] In some embodiments of the present invention, the monomer A includes at least one of acrylic acid, lithium acrylate, and sodium acrylate, but is not limited thereto. The purpose of adding monomer A is to provide -COOR 1 , R 1 Selected from H, Li or Na, those skilled in the art can independently select a suitable monomer A according to their needs, which should be regarded as a reasonable change within the scope of the present invention.
[0023] In some embodiments of the present invention, the monomer B includes at least one of methyl acrylate, ethyl acrylate, and butyl acrylate, but is not limited thereto. 1 ~C 10 The purpose of adding monomer B is to provide -COOR 2 , R 2 is selected from substituted or unsubstituted C 1 ~C 10 Those skilled in the art can select suitable monomer B according to their needs, which should be regarded as reasonable changes within the scope of the present invention.
[0024] In some embodiments of the present invention, in step S1, distilled water is added to the reaction container, stirring is started, and high-purity nitrogen is introduced for deoxygenation.
[0025] In some embodiments of the present invention, in step S2, acrylonitrile is added to provide -COOR 1 Monomer A, providing -COOR 2 After adding monomer B, heat to 65°C under an inert atmosphere and keep the temperature constant.
[0026] In some embodiments of the present invention, the initiator includes 20% ammonium persulfate, but is not limited thereto.
[0027] In a second aspect of the present invention, a water-based safety coating is provided, wherein the raw materials of the water-based safety coating include the polyacrylate binder as described above, a first conductive agent and an inorganic filler.
[0028] The water-based safety coating according to the embodiment of the present invention has at least the following beneficial effects: the water-based safety coating provided by the present invention can obtain a water-based safety coating with good safety performance and cycle performance by limiting the molecular weight of the binder in the coating and the content of cyano, ester and carboxylate groups in the molecular chain, while being able to improve the high and low temperature discharge performance and cycle performance. The above-mentioned water-based safety coating can be introduced into the electrode sheet, which can not only improve the safety performance and cycle performance of the battery, but also significantly improve the high and low temperature discharge performance and rate discharge performance of the battery.
[0029] In some embodiments of the present invention, the mass percentage of the polyacrylate binder in the water-based safety coating is 1wt%~24wt%, preferably 10wt%~15wt%. When the amount of binder is less than 1wt%, the water-based safety coating has insufficient adhesion and is prone to fall off during later use; when the amount of binder is greater than 24wt%, the water-based safety coating will be difficult to process during gravure printing and will also deteriorate the internal resistance of the battery cell.
[0030] In some embodiments of the present invention, the water-based safety coating comprises at least one of the following: A1) the mass ratio of the first conductive agent, the polyacrylate binder, and the inorganic filler is (0.5-5): (1-24): (71-98.5); A2) the mass percentage of the first conductive agent to the water-based safety coating is 0.5% to 5%, preferably 1.5 to 3; A3) The inorganic filler has a median particle size range of 0.2 to 4 μm and a specific surface area of 5 to 50 m 2 / g; A4) The raw materials of the water-based safety coating further include a heat-stable active substance; A5) When A4) is included, the mass ratio of the first conductive agent, the polyacrylate binder, the inorganic filler, and the thermally stable active substance is (0.5-5): (1-24): (1-97.5): (1-97.5); A6) When A4) is included, the thermally stable active material includes one or both of lithium iron phosphate and lithium manganese iron phosphate.
[0031] In some embodiments of the present invention, the mass ratio of the first conductive agent, the polyacrylate binder, and the inorganic filler is (0.5-5): (1-24): (71-98.5). For example, in terms of weight, the first conductive agent can be 0.5-5 parts, preferably 1.5-3 parts, the binder can be 1-25 parts, preferably 10-15 parts, and the inorganic filler can be 71-98.5 parts.
[0032] In some embodiments of the present invention, the mass percentage of the first conductive agent in the water-based safety coating is 0.5% to 5%, preferably 1.5% to 3%. If the conductive agent content is too low, the water-based safety coating film resistance will be too large and the battery cell cycle performance will be poor; if the content is too high, the water-based safety coating film resistance will be too low and the battery cell safety will be poor. When the content of the conductive agent is between 0.5wt% and 5wt%, both safety and cycle can be taken into account.
[0033] In some embodiments of the present invention, the first conductive agent includes at least one of acetylene black, graphene, graphyne, carbon nanotubes, carbon fibers, and conductive carbon black. The present invention has no special requirements for the first conductive agent, and any conventional conductive agent in the art can be used, such as conductive carbon black or carbon nanotubes, and more specifically, super dense high conductive carbon black SUPER P Li.
[0034] In some embodiments of the present invention, the inorganic filler is selected from at least one of aluminum oxide, boehmite, aluminum hydroxide, magnesium hydroxide, titanium dioxide, silicon dioxide, zirconium oxide, barium titanate, lithium niobate, yttrium-doped zirconium oxide, gadolinium-doped cerium oxide, montmorillonite, aluminosilicate, lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide, lithium lanthanum zirconium niobium oxide, lithium aluminum titanium phosphate, lithium germanium titanium phosphate, and lithium lanthanum titanate. The present invention has no special requirements for the inorganic filler, and conventional inert inorganic fillers in the art can be used. Considering the cost and processability, the inorganic filler can include one or two of aluminum oxide, boehmite, aluminum hydroxide, and magnesium hydroxide, preferably boehmite.
[0035] In some embodiments of the present invention, the median particle size D of the inorganic filler is v50 The range is 0.2~4μm, and the specific surface area is 5~50m 2 / g. When the inorganic filler D v50 Less than 0.2μm, and the specific surface area is greater than 50m 2 / g, the inorganic filler is prone to agglomeration and difficult to disperse; when the inorganic filler D v50 Greater than 4μm, and specific surface area less than 5m 2 / g, it is difficult to obtain a thinner safety coating due to the large particle size, which affects the energy density of the battery cell. When the median particle size and specific surface area of the inorganic filler are within the above range, a better balance can be achieved between the processability of the water-based safety coating and the energy density of the battery cell.
[0036] In some embodiments of the present invention, the raw materials of the water-based safety coating further include a thermally stable active substance.
[0037] In some embodiments of the present invention, the mass ratio of the first conductive agent, the polyacrylate binder, the inorganic filler, and the thermally stable active substance is (0.5-5): (1-24): (1-97.5): (1-97.5).
[0038] In some embodiments of the present invention, the raw materials of the water-based safety coating include the above-mentioned binder, the first conductive agent, the inorganic filler and the thermally stable active substance, and the mass ratio thereof satisfies: the first conductive agent: the binder: the inorganic filler: the thermally stable active substance = (0.5~5): (1~24): (1~97.5): (1~97.5). For example, in terms of weight parts, the first conductive agent can be 0.5~5 parts, the binder can be 1~24 parts, the inorganic filler can be 1~97.5 parts, and the thermally stable active substance can be 1~97.5 parts. In some embodiments of the present invention, the thermally stable active substance includes one or both of lithium iron phosphate and lithium manganese iron phosphate.
[0039] According to a third aspect of the present invention, an electrode sheet is provided, comprising: a current collector, an active material layer and a water-based safety coating, wherein the raw materials of the water-based safety coating include the above-mentioned polyacrylate binder, a first conductive agent and an inorganic filler.
[0040] The electrode sheet according to the embodiment of the present invention has at least the following beneficial effects: The present invention provides an electrode sheet including a water-based safety coating, and by limiting the molecular weight of the binder in the water-based safety coating and the relevant parameters such as the content of cyano, ester and carboxylate groups in the molecular chain, a water-based safety coating with good safety performance and cycle performance is obtained, while being able to improve high and low temperature discharge performance and cycle performance. Introducing the above-mentioned water-based safety coating into the electrode sheet can not only improve the safety performance and cycle performance of the battery, but also significantly improve the high and low temperature discharge performance and rate discharge performance of the battery.
[0041] In some embodiments of the present invention, the aqueous safety coating is coated on at least one surface of the current collector, and the active material layer is coated on a surface of the aqueous safety coating away from the current collector and / or on a surface of the current collector away from the aqueous safety coating.
[0042] Specifically, the electrode sheet is a positive electrode sheet, the water-based safety coating is coated on at least one side of the current collector, and the active material layer is coated on the side of the water-based safety coating away from the current collector and / or on the side of the current collector away from the water-based safety coating.
[0043] More specifically, the electrode sheet is a positive electrode sheet, the water-based safety coating is coated on both side surfaces of the current collector, and the active material layer is coated on the surface of the water-based safety coating away from the current collector.
[0044] In other embodiments of the present invention, the active material layer is coated on at least one side surface of the current collector, and the aqueous safety coating is coated on the side surface of the active material layer away from the current collector and / or on the side surface of the current collector away from the active material layer.
[0045] Specifically, the electrode sheet is a negative electrode sheet, the active material layer is coated on at least one side of the current collector, and the aqueous safety coating is coated on the side of the active material layer away from the current collector and / or on the side of the current collector away from the active material layer.
[0046] More specifically, the electrode sheet is a negative electrode sheet, the active material layer is coated on both side surfaces of the current collector, and the water-based safety coating is coated on the surface of the active material layer away from the current collector.
[0047] The electrode sheet provided by the present invention can be used as a positive electrode sheet or a negative electrode sheet, preferably a positive electrode sheet. When used as a positive electrode sheet, the water-based safety coating is closer to the current collector, and its structure is "current collector-water-based safety coating-active material layer", such as Figure 1 As shown, the positive electrode sheet 01 includes the following structures: a current collector 022; a water-based safety coating 023, which is disposed on at least one surface of the current collector 022; and an active material layer 011, which is disposed on the surface of the water-based safety coating 023 away from the current collector 022. When used as a negative electrode sheet, the active material layer is closer to the current collector, and its structure is "current collector-active material layer-water-based safety coating".
[0048] The internal short circuit of lithium-ion batteries can generally be divided into several types: 1) short circuit between positive and negative current collectors; 2) short circuit between positive and negative active materials; 3) short circuit between negative active material and positive current collector; 4) short circuit between positive active material and negative current collector. Among them, the impedance of the short circuit point between the negative active material and the positive current collector is small, and the trigger temperature of the negative exothermic reaction is low. Therefore, the short circuit between the negative active material and the Al foil is the most dangerous. The present invention introduces the above-mentioned binder as a raw material of the water-based safety coating into the electrode sheet, and introduces a water-based safety coating with high bonding force to the surface of the positive current collector. Based on its excellent bonding performance, the water-based safety coating can be firmly adhered to the current collector surface of the electrode sheet, which can not only reduce the surface contact resistance, but also reduce the generation of positive current collector burrs when the battery cell is subjected to safety testing, and reduce the contact short circuit between the positive current collector burrs and the unstable negative active material in the charging state, thereby effectively improving the safety of the battery cell.
[0049] In some embodiments of the present invention, the thickness of the water-based safety coating is 1-20 μm, for example, 1-7 μm, 7-14 μm, or 14-20 μm.
[0050] In some embodiments of the present invention, the coating surface density of the water-based safety coating is 2-35 mg / 1540.25 mm 2 . For example, it can be 2~8 mg / 1540.25mm 2 , 8~15 mg / 1540.25mm 2 , 14~21 mg / 1540.25mm 2 , 20~28 mg / 1540.25mm 2 , 28~35 mg / 1540.25mm 2 .
[0051] There is a positive correlation between the coating surface density of the water-based safety coating and its thickness. If the thickness is too low, the safety performance of the battery cell will be poor; if the thickness is too large, the energy density of the battery cell will be reduced.
[0052] In some embodiments of the present invention, the membrane resistance of the water-based safety coating at a test pressure of 0.4 t is 0.5~5Ω, for example, 0.5~2Ω, 2~3.5Ω, 3.5~5Ω. The membrane resistance of the water-based safety coating is the primary factor affecting the safety performance of the battery cell. If the value is too small, the safety performance of the battery cell will deteriorate, and if it is too large, the cycle performance of the battery cell will deteriorate. The value is between 0.5~5Ω@0.4T, which can take into account both safety performance and cycle performance.
[0053] In some embodiments of the present invention, the bonding force between the water-based safety coating and the current collector is not less than 100 N / m. If the bonding force is less than 100 N / m, there is a risk that the water-based safety coating will fall off during subsequent use.
[0054] In some embodiments of the present invention, the raw materials of the active material layer include active material, a second conductive agent and a second binder.
[0055] In some embodiments of the present invention, the mass percentage of the active material in the active material layer is 90% to 98%.
[0056] In some embodiments of the present invention, the mass percentage of the second conductive agent in the active material layer is 0.5% to 5%, preferably 0.5% to 2%. If the content of the second conductive agent is too low, the battery cell cycle performance is poor; if the content is too high, it is good for improving the cycle performance, but will lead to poor safety performance of the battery cell.
[0057] In some embodiments of the present invention, the second conductive agent includes at least one of acetylene black, graphene, graphyne, carbon nanotubes, carbon fibers, and conductive carbon black. The present invention has no special requirements for the second conductive agent, and any conventional conductive agent in the art can be used, such as conductive carbon black or carbon nanotubes, and more specifically, super dense high conductive carbon black SUPER P Li.
[0058] In some embodiments of the present invention, the mass percentage of the second binder in the active material layer is 0.5% to 5%. If the amount of the second binder is too little, the active material layer will not have sufficient bonding strength and will easily fall off during later use; if the amount of the second binder is too much, the active material layer will be difficult to process and the internal resistance of the battery cell will also be deteriorated.
[0059] In some embodiments of the present invention, the second binder includes at least one of polyvinylidene fluoride PVDF, sodium carboxymethyl cellulose CMC, styrene butadiene rubber SBR, and PAA-based binders. The present invention has no special requirements for the second binder, and any conventional binder in the art can be used.
[0060] In a specific embodiment, the active material layer may be a positive electrode active material layer, and the raw materials of the positive electrode active material layer include a positive electrode active material, a second conductive agent, and a second binder.
[0061] The positive electrode active material is not limited, and can be one or more of common lithium cobalt oxide, lithium iron phosphate and ternary materials, and the amount used is 90wt% to 98wt% of the total weight of the active material layer. Under the condition of ensuring that the active material has a certain conductivity and adhesion, the higher the content of the active material, the better, so that the battery cell has a higher energy density.
[0062] The second binder is not limited and can be a common cathode binder, including polyvinylidene fluoride PVDF, sodium carboxymethyl cellulose CMC and PAA binders, and the amount used is 0.5wt%~5wt% of the total weight of the active material layer. If the amount of the second binder is too little, the active material layer will not have enough adhesion and will easily fall off during later use; if the amount of the second binder is too much, the active material layer will be difficult to process and the internal resistance of the battery will also be deteriorated. Considering that it does not directly contact the current collector, the upper limit of its amount can be appropriately reduced to ensure that the positive active material does not fall off during the use of the battery. At the same time, a lower amount can also improve the cycle performance of the battery, increase the amount of positive active material, and improve the energy density of the battery.
[0063] In a specific embodiment, the active material layer may be a negative electrode active material layer, and the raw materials of the negative electrode active material layer include a negative electrode active material, a second conductive agent, and a second binder.
[0064] The negative electrode active material is not limited and can be one or more of common artificial graphite, natural graphite, modified graphite, silicon oxide compounds, silicon carbon composites and other silicon negative electrode materials, and the amount used is 90wt%~98wt% of the total weight of the active material layer.
[0065] In some embodiments of the present invention, the electrode sheet further includes a current collector. The current collector is not limited and can be a common current collector. For example, when the electrode sheet is a positive electrode sheet, the current collector can be an aluminum foil or a composite aluminum foil; when the electrode sheet is a negative electrode sheet, the current collector can be a copper foil or a composite copper foil.
[0066] In some preferred embodiments of the present invention, the dyne value of the current collector is ≥30 dyn / cm, preferably ≥38 dyn / cm.
[0067] In some embodiments of the present invention, the water-based safety coating is coated on both sides of the current collector, and the water-based safety coating satisfies at least one of the following conditions: B1) the double-sided thickness of the water-based safety coating is 1 to 20 μm; B2) The double-sided coating density of the water-based safety coating is 2-35 mg / 1540.25 mm 2 ; B3) The double-sided membrane resistance of the water-based safety coating tested under a pressure of 0.4 t is 0.5~5Ω; B4) The double-sided thickness d of the water-based safety coating and the value of the double-sided membrane resistance R under a pressure of 0.4 t satisfy the condition: 2≤R×d≤50; B5) The water-based safety coating is coated on both sides of the current collector. The distance W between the left edge of the water-based safety coating on the A side of the current collector and the left edge of the current collector is perpendicular to the unwinding direction of the current collector. A1 The range is 2mm~30mm, and the distance W between the right edge and the right edge of the current collector is A2 The range is 2mm~30mm; the distance W between the left edge of the water-based safety coating on the B side of the current collector and the left edge of the current collector B1 The range is 3mm~30mm, and the distance W between the right edge and the right edge of the current collector is B2 The range is 3mm~30mm; and W B1 -W A1 ≥1mm, W B2 -W A2 ≥1mm.
[0068] In some embodiments of the present invention, the double-sided thickness d of the aqueous safety coating (i.e., the sum of the thicknesses of the aqueous safety coating coated on both sides of the current collector surface) is 1-20 μm, for example, 1-7 μm, 7-14 μm, or 14-20 μm.
[0069] In some embodiments of the present invention, the double-sided coating density of the water-based safety coating (i.e., the sum of the coating surface densities of the water-based safety coating coated on both sides of the current collector surface) is 2-35 mg / 1540.25 mm 2 . For example, it can be 2~8mg / 1540.25mm 2 ,8~15mg / 1540.25mm 2 , 14~21mg / 1540.25mm 2 20~28mg / 1540.25mm 2 , 28~35mg / 1540.25mm 2 .
[0070] There is a positive correlation between the coating surface density of the water-based safety coating and its thickness. If the thickness is too low, the safety performance of the battery cell will be poor; if the thickness is too large, the energy density of the battery cell will be reduced.
[0071] In some embodiments of the present invention, the double-sided membrane resistance R of the water-based safety coating under a pressure of 0.4 t (i.e., the sum of the membrane resistances of the water-based safety coating on both sides of the current collector surface) is 0.5~5Ω, for example, 0.5~2Ω, 2~3.5Ω, 3.5~5Ω. The membrane resistance of the water-based safety coating is the primary factor affecting the safety performance of the battery cell. If the value is too small, the safety performance of the battery cell will deteriorate, and if it is too large, the cycle performance of the battery cell will deteriorate. The value is between 0.5~5Ω@0.4T, which can take into account both safety performance and cycle performance.
[0072] In some embodiments of the present invention, the double-sided thickness d (in μm) of the water-based safety coating and the double-sided membrane resistance R (in Ω) under a pressure of 0.4 t satisfy the condition: 2≤R×d≤50. Generally speaking, the parameters R and d are positively correlated with the safety of the battery cell, and negatively correlated with the cycle performance of the battery cell. When the relationship 2≤R×d≤50 is satisfied, a better balance can be achieved between the safety performance and electrochemical performance of the battery cell.
[0073] In some embodiments of the present invention, the bonding force between the water-based safety coating and the current collector is not less than 100 N / m. If the bonding force is less than 100 N / m, there is a risk that the water-based safety coating will fall off during subsequent use.
[0074] In a specific embodiment, the present invention provides a positive electrode sheet, the positive electrode sheet comprising a positive electrode active material layer, a water-based safety coating and a positive electrode current collector. The water-based safety coating contains the aforementioned water-soluble binder, and the structural formula of the binder is: ; Among them, R 1 Each occurrence is independently selected from H, Li, Na; R 2 Each occurrence is independently selected from substituted or unsubstituted C 1 ~C 10 and 5≤(x+z) / y≤20, 1.2≤z / x≤2, and x, y, and z are not 0.
[0075] The electrolyte absorption rate of the binder at 80° C. is 10% to 50%.
[0076] The aqueous safety coating is coated on both side surfaces of the current collector.
[0077] The double-sided thickness d of the water-based safety coating is 1-20 μm.
[0078] The double-sided membrane resistance R of the water-based safety coating under a pressure of 0.4 t is 0.5-5Ω.
[0079] The double-sided thickness d (in μm) of the water-based safety coating and the double-sided diaphragm resistance R (in Ω) under a pressure of 0.4 t satisfy the condition: 2≤R×d≤50.
[0080] The present invention overcomes the problems of poor low-temperature discharge performance and rate discharge performance of conventional water-based coatings by limiting the content relationship of various groups contained in the side chain of the binder and selecting the electrolyte absorption rate c (10%≤c≤50%). At the same time, the water-based safety coating also maintains the advantages of conventional water-based safety coatings and can firmly adhere to the surface of the current collector, which can not only reduce the surface contact resistance, but also reduce the generation of positive current collector burrs when the battery cell is safety tested, and reduce the contact short circuit between the positive current collector burrs and the unstable negative active material in the charging state, thereby improving the safety of the battery cell. In addition, the resistance and thickness of the double-sided membrane after the water-based safety coating is applied are also limited, so as to achieve a balance between the safety performance and cycle performance of the battery cell.
[0081] In a fourth aspect of the present invention, a method for preparing the above-mentioned electrode sheet is provided, comprising the steps of: S100, mixing a polyacrylate adhesive with water and performing gluing to obtain a glue solution; S200, uniformly mixing the first conductive agent and the inorganic filler with the glue, or uniformly mixing the first conductive agent, the thermally stable active substance and the inorganic filler with the glue to obtain a water-based safety coating slurry; S300, coating the aqueous safety coating slurry onto one or both sides of the current collector, or onto the surface of the active material layer away from the current collector, to obtain the electrode sheet.
[0082] The method for preparing the electrode sheet according to the embodiment of the present invention has at least the following beneficial effects: by introducing a water-based safety coating into the electrode sheet and limiting the parameters of the binder and the coating, the present invention can take into account both the safety performance and cycle performance of the battery cell without changing the original process, and improve the low-temperature discharge performance and rate discharge performance. This method is not only simple in process, but also has non-harsh reaction conditions, is compatible with the original preparation process, and has the potential for large-scale application.
[0083] In some embodiments of the present invention, the preparation method comprises at least one of the following: C1) The mass ratio of the first conductive agent, the polyacrylate binder, and the inorganic filler is (0.5-5): (1-24): (71-98.5); C2) the solid content of the glue is 10% to 30%; C3) The viscosity of the glue is 1×10 3 ~3×10 4 mPa·s; C4) The solid content of the water-based safety coating slurry is ≥ 10%; C5) the viscosity of the aqueous safety coating slurry is ≥50 mPa·s; C6) the dyne value of the current collector is ≥30 dyn / cm; C7) applying the aqueous safety coating slurry to one or both sides of the current collector, or the surface of the active material layer away from the current collector, by gravure printing; C8) When C7) is included, the oven temperature during gravure printing is 90-110°C and the printing speed is 10-50 m / min; C9) The mass ratio of the first conductive agent, polyacrylate binder, inorganic filler and thermally stable active substance is (0.5~5):(1~24):(1~97.5):(1~97.5).
[0084] In some embodiments of the present invention, the mass ratio of the first conductive agent, the polyacrylate binder, and the inorganic filler is (0.5-5): (1-24): (71-98.5). For example, in terms of weight, the first conductive agent can be 0.5-5 parts, the binder can be 1-24 parts, and the inorganic filler can be 71-98.5 parts.
[0085] In some embodiments of the present invention, the solid content of the glue solution is 10% to 30%, for example, 10% to 20%, 20% to 25%, or 25% to 30%.
[0086] In some embodiments of the present invention, the viscosity of the glue is 1×10 3 ~3×10 4 mPa·s, preferably 1.5×10 4 ~2.5×10 4 mPa·s, more preferably 1.6×10 4 ~2.2×10 4 mPa·s, for example, can be 2×10 4 mPa·s.
[0087] If the solid content and viscosity of the adhesive liquid are too low, it will not only reduce the processing efficiency, but may also cause insufficient adhesion of the water-based safety coating; if the solid content and viscosity are too high, it may make the processing of the water-based safety coating difficult.
[0088] In some embodiments of the present invention, the raw materials of the water-based safety coating further include a heat-stable active substance, and the mass ratio thereof satisfies: first conductive agent: binder: inorganic filler: heat-stable active substance = (0.5-5): (1-24): (1-97.5): (1-97.5). For example, in terms of weight, the first conductive agent may be 0.5-5 parts, the binder may be 1-24 parts, the inorganic filler may be 1-97.5 parts, and the heat-stable active substance may be 1-97.5 parts.
[0089] In some embodiments of the present invention, the solid content of the aqueous safety coating slurry is ≥10%, preferably 10% to 21%.
[0090] In some embodiments of the present invention, the viscosity of the aqueous safety coating slurry is ≥50 mPa·s.
[0091] The solid content of the water-based safety coating slurry should not be less than 10%, and the viscosity should not be less than 50 mPa·s. Too low solid content will not only reduce the production efficiency, but also make it difficult to obtain a water-based safety coating with a specified thickness and surface density, while too low viscosity will be detrimental to the gravure printing process.
[0092] In some embodiments of the present invention, the dyne value of the current collector is ≥30 dyn / cm, preferably ≥38 dyn / cm. When the dyne value of the current collector is lower than 30 dyn / cm, on the one hand, it is not conducive to the wetting of the current collector by the water-based safety coating slurry, resulting in leakage of the primer, and on the other hand, it will reduce the adhesion between the water-based safety coating and the current collector, causing the water-based safety coating to easily fall off during subsequent use, which has an adverse effect on the safety of the battery cell. The dyne value of the current collector is not less than 38 dyn / cm, which can ensure that the primer has a good appearance and morphology, and the adhesion between the water-based safety coating and the current collector is good.
[0093] In some embodiments of the present invention, the aqueous safety coating slurry is coated on one or both surfaces of the current collector, or on the surface of the active material layer away from the current collector, by gravure printing.
[0094] In some embodiments of the present invention, the temperature of the oven during gravure printing is 90-110° C.; the printing speed is not less than 10 m / min, preferably 10-50 m / min.
[0095] When gravure printing is performed, the oven temperature should be 90~110℃ and the printing speed should be 10~50 m / min. If the oven temperature is lower than 90℃, the production efficiency will be reduced. If it is higher than 110℃, there may be problems such as cracking and migration of the conductive agent to the surface. If the printing speed is too low, the production efficiency will also be reduced. If it is too high, the water-based safety coating will be missed, which will have a negative impact on the safety performance of the battery cell.
[0096] In a specific embodiment of the present invention, a method for preparing the above-mentioned electrode sheet is provided, comprising the following steps: (1) Using deionized water as a solvent, adding a binder to form a glue solution with a suitable viscosity and solid content, then adding a first conductive agent and an inorganic filler into the glue solution and mixing evenly to obtain a water-based safety coating slurry; (2) The aqueous safety coating slurry obtained in step (1) is transferred to one or both sides of the current collector, or to the surface of the active material layer away from the current collector, by gravure printing, to obtain an electrode sheet in which the aqueous safety coating area and the non-aqueous safety coating area are alternately arranged along the unwinding direction of the electrode sheet.
[0097] In some embodiments of the present invention, the total length of the electrode sheet containing the water-based safety coating is L, and the length of the water-based safety coating area is L 1 , the length of the non-aqueous safety coating area is L 2 , and L 1 >L 2 , L 1 +L 2 =L.
[0098] In some embodiments of the present invention, a water-based safety coating may be applied to both sides (side A and side B) of the electrode sheet, wherein the length of the water-based safety coating area on side A is L A1 , the length of the non-aqueous safety coating area is L A2 , and L A1 >L A2 , L A1 +L A2 =L A ; The length of the safety coating area on the B surface is L B1 , the length of the non-aqueous safety coating area is L B2 , and L B1 >L B2 , L B1 +L B2 =L B .
[0099] In some preferred embodiments of the present invention, in order to improve production efficiency and reduce costs, LA 2 and LB 2 All are set to 0, that is, L A1=L B1 =L A =L B .
[0100] In some embodiments of the present invention, when applying the water-based safety coating, it is also necessary to reserve N in the water-based safety coating area or the non-aqueous safety coating area along the unwinding direction of the electrode sheet. 1 Slots for tab welding, N 1 ≥0.
[0101] In some embodiments of the present invention, when applying the water-based safety coating, it is also necessary to reserve N in the water-based safety coating area or the non-aqueous safety coating area perpendicular to the unwinding direction of the electrode sheet. 2 Slots for tab welding, N 2 ≥0.
[0102] In some embodiments of the present invention, when applying the water-based safety coating, N can also be applied simultaneously along the unwinding direction of the electrode sheet. 3 Water-based safety coating, N 3 ≥1.
[0103] In some embodiments of the present invention, if both sides of the electrode sheet are coated with a safety coating, the slots reserved for the electrode tab welding need to keep the A / B side slots opposite to each other, and the horizontal and vertical offset distances are None exceed 2mm.
[0104] In some embodiments of the present invention, if both sides of the electrode sheet are coated with a safety coating, the distance between the left edge of the water-safe surface A and the left edge of the current collector is W along the direction perpendicular to the unwinding direction of the current collector. A1 (That is, the left side of A is blank as W A1 ), the blank on the right side of A is W A2 , the left side of B is blank for W B1 , the blank on the right side of B is W B2 , satisfying 2mm≤W A1 , W A2 ,W B1 , W B2 ≤30mm, and W B1 -W A1 ≥1mm, W B2 -W A2 ≥1mm.
[0105] In some embodiments of the present invention, the electrode sheet is a positive electrode sheet, and the method for preparing the positive electrode sheet comprises the steps of: (10) Using deionized water as a solvent, adding a binder to form a glue solution with a suitable viscosity and solid content, then adding a first conductive agent and an inorganic filler to the glue solution and mixing them evenly, or mixing the first conductive agent, a thermally stable active substance and an inorganic filler with the glue solution evenly to obtain a water-based safety coating slurry; (20) The aqueous safety coating slurry obtained in step (10) is transferred to one or both sides of the current collector by gravure printing to obtain a positive electrode sheet in which the aqueous safety coating area and the non-aqueous safety coating area are alternately arranged along the unwinding direction of the current collector.
[0106] Among them, the non-aqueous safety coating area corresponds to the head and / or tail of the positive electrode sheet of the battery cell, usually one side of which is an active material and the other side is a blank foil, or a separately set ceramic layer. The ceramic layer usually contains only inorganic fillers and binders, which can reduce the generation of positive current collector burrs in the non-aqueous safety coating area during battery cell testing, reduce the probability of contact between the positive current collector and the negative active material, and thus improve the safety performance of the battery cell. However, the ceramic layer needs to be coated in an additional process after the safety coating is set, which not only reduces production efficiency, but also increases production costs.
[0107] In some embodiments of the present invention, the total length of the positive electrode sheet containing the water-based safety coating is L, and the length of the water-based safety coating area is L 1 , the length of the non-aqueous safety coating area is L 2 , and L 1 >L 2 , L 1 +L 2 =L.
[0108] In some embodiments of the present invention, a water-based safety coating may be applied to both sides (side A and side B) of the positive electrode sheet, wherein the length of the water-based safety coating area on side A is L. A1 , the length of the non-aqueous safety coating area is L A2 , and L A1 >L A2 , L A1 +L A2 =L A ; The length of the safety coating area on the B surface is L B1 , the length of the non-aqueous safety coating area is L B2 , and L B1 >L B2 , L B1 +L B2 =L B .
[0109] In some preferred embodiments of the present invention, in order to improve production efficiency and reduce costs, the function of the ceramic layer can be assumed by the water-based safety coating, that is, the non-aqueous safety coating area is also provided with a water-based safety coating. A2 and L B2 are all set to 0, that is, L A1 =L B1 =L A =L B .
[0110] Figure 2 The figure shows a cross-sectional view of a current collector coated with a water-based safety coating along the unwinding direction in one of the specific embodiments of the present invention. In the figure, 02-positive current collector with safety coating; 021-reserved slot; 022-current collector; 023-water-based safety coating; 024-non-safety coating area. The water-based safety coating area and the non-water-based safety coating area on the A side and the B side of the positive electrode sheet can be arranged relative to each other, such as Figure 2 (a); it is also possible to set a non-aqueous safety coating area on one side and a water-based safety coating area on the other side, such as Figure 2 As shown in (b), the total length of the current collector containing the water-based safety coating is L, and the length of the water-based safety coating area on the B surface is L B1 , the length of the non-aqueous safety coating area is L B2 , and L B1 >L B2 , L B1 +L B2 =L B =L A1 =L A =L; the non-aqueous safety coating area can also be provided with a water-based safety coating, L A2 and L B2 are all set to 0, that is, L A1 =L B1 =L A =L B ,like Figure 2 Middle (c).
[0111] In some embodiments of the present invention, when applying the water-based safety coating, it is also necessary to reserve N in the water-based safety coating area or the non-aqueous safety coating area along the unwinding direction of the current collector. 1 Slots for tab welding, N 1 ≥0.
[0112] In some embodiments of the present invention, when applying the water-based safety coating, it is also necessary to reserve N in the water-based safety coating area or the non-aqueous safety coating area perpendicular to the unwinding direction of the current collector. 2 Slots for tab welding, N 2 ≥0.
[0113] In some embodiments of the present invention, when applying the water-based safety coating, N3 strips of water-based safety coating may be applied simultaneously along the unwinding direction of the current collector. 3 ≥1.
[0114] When the water-based safety coating is applied, the slot for the electrode ear welding may be reserved or not reserved as required, such as Figure 3 shown.
[0115] In some embodiments of the present invention, if both sides of the current collector are coated with a safety coating, the slots on the A / B sides must be kept relative to each other when reserving slots for electrode tab welding, and the lateral and longitudinal misalignments ∆W must not exceed 2 mm.
[0116] In some embodiments of the present invention, the water-based safety coating is applied to both sides of the current collector, and the distance W between the left edge of the water-based safety coating on the A side of the current collector and the left edge of the current collector is perpendicular to the unwinding direction of the current collector. A1 The range is 2mm~30mm, and the distance W between the right edge and the right edge of the current collector is A2 The range is 2mm~30mm; the distance W between the left edge of the water-based safety coating on the B side of the current collector and the left edge of the current collector B1 The range is 3mm~30mm, and the distance W between the right edge and the right edge of the current collector is B2 The range is 3mm~30mm; and W B1 -W A1 ≥1mm, W B2 -W A2 That is to say, if both sides of the current collector are coated with a safety coating, the distance from the left edge of the water-safe surface on the A side to the left edge of the current collector along the direction perpendicular to the unwinding direction of the current collector is W. A1 (That is, the left side of A is blank as W A1 ), the blank on the right side of A is W A2 , the left side of B is blank for W B1 , the blank on the right side of B is W B2 , satisfying 2mm≤W A1 , W A2 ≤30mm, 3mm≤W B1 , W B2 ≤30mm, and W B1 -W A1 ≥1mm, W B2 -W A2 ≥1mm. Figure 4The figure shows a cross-sectional view of the water-based safety coating perpendicular to the unwinding direction in a specific embodiment of the present invention. In the figure, 021-reserved slot; 022-current collector; 023-water-based safety coating; such an arrangement enables the width of the water-based safety coating on side A to be more than 2 mm wider than that on side B, thereby reducing the bulging of the edge of the primer when it is rolled up.
[0117] In the fifth aspect of the present invention, a lithium-ion battery is proposed, comprising a positive electrode sheet, a negative electrode sheet, and a separator separated between the positive electrode sheet and the negative electrode sheet; the positive electrode sheet and / or the negative electrode sheet is the electrode sheet as described above or the electrode sheet obtained by the preparation method as described above.
[0118] Since the lithium-ion battery adopts all the technical solutions of the electrode sheet of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment. That is, the lithium-ion battery introduces a water-based safety coating into the electrode sheet and limits the molecular weight of the binder in the water-based safety coating and the content of cyano, ester and carboxylate groups in the molecular chain, etc., to obtain a water-based safety coating with good safety performance and cycle performance, and can improve high and low temperature discharge performance and cycle performance, which can not only improve the safety performance and cycle performance of the battery, but also significantly improve the high and low temperature discharge performance and rate discharge performance of the battery.
[0119] In some embodiments of the present invention, the positive electrode sheet is an electrode sheet as described above. The positive electrode sheet includes the positive electrode current collector containing the water-based safety coating and a positive electrode active material layer coated on at least one surface of the positive electrode current collector. The positive electrode current collector is a common positive electrode current collector in the art, such as aluminum foil, but not limited thereto. The positive electrode active material layer includes a positive electrode active material, which is a common positive electrode active material currently used in lithium-ion batteries, including but not limited to a chemical formula such as Li x Ni h Co y M z O 2-d N d (wherein 0.95≤x≤1.2, h>0, y≥0, z≥0, and h+y+z=1, 0≤d≤1, M is selected from a combination of one or more of Mn and Al, and N is selected from a combination of one or more of F, P, and S) The positive electrode active material may also be, but is not limited to, LiCoO 2 、LiNiO 2 、LiVO 2 、LiCrO 2 、LiMn 2 O 4 、LiCoMnO 4 , Li 2 NiMn 3 O8 、LiNi 0.5 Mn 1.5 O 4 、LiCoPO 4 、LiMnPO 4 、LiFePO 4 、LiNiPO 4 、LiCoFSO 4 , CuS 2 , FeS 2 、MoS 2 、NiS、TiS 2 The positive electrode active material may also be subjected to a modification treatment. The method for modifying the positive electrode active material should be known to those skilled in the art. For example, the positive electrode active material may be modified by coating, doping, etc. The material used for the modification treatment may include but is not limited to a combination of one or more of Al, B, P, Zr, Si, Ti, Ge, Sn, Mg, Ce, W, etc.
[0120] In some embodiments of the present invention, the negative electrode sheet is an electrode sheet as described above. The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector. The negative electrode current collector has no special requirements and can be a copper foil commonly used in the industry. The negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes a silicon-based material, which can be selected from one or more of elemental silicon, silicon oxide compounds, silicon carbon composites, and silicon alloys, or a mixture of silicon negative electrode materials and other commonly used negative electrode active materials. The other negative electrode active materials include but are not limited to one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, tin-based materials, lithium titanate or other metals that can form alloys with lithium. Among them, the graphite can be selected from one or more of artificial graphite, natural graphite and modified graphite; the tin-based material can be selected from one or more of elemental tin, tin oxide compounds, and tin alloys.
[0121] In some embodiments of the present invention, the diaphragm may be any material suitable for lithium-ion battery diaphragms in the art, for example, it may be a combination of one or more of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fiber, etc. In actual production, the material and structure of the diaphragm are not strictly limited, for example, it may be a multi-layer structure formed by stacking the above materials, it may be a single-layer structure formed by mixing the above materials, or it may be a single-layer structure formed by a single material; as long as it can play the basic role of a diaphragm.
[0122] In some embodiments of the present invention, the lithium battery further comprises an electrolyte, wherein the electrolyte infiltrates the positive electrode, the negative electrode and the separator. The electrolyte comprises an organic solvent, an electrolyte lithium salt and an additive. The electrolyte lithium salt may be LiPF used in a high temperature electrolyte. 6 and / or LiBOB; it can also be LiBF used in low temperature electrolytes 4 、LiBOB、LiPF 6 It can also be LiBF used in the overcharge-proof electrolyte 4 、LiBOB、LiPF 6 , LiTFSI; or LiClO 4 、LiAsF 6 、LiCF 3 SO 3 、LiN(CF 3 SO 2 ) 2 At least one of the above. The organic solvent may be a cyclic carbonate, including PC, EC; a chain carbonate, including DEC, DMC or EMC; or a carboxylic acid ester, including PP, MA, EA, EP, etc. The additives include but are not limited to film-forming additives, conductive additives, flame retardant additives, overcharge prevention additives, and additives for controlling H in the electrolyte. 2 At least one of an additive for increasing the content of O and HF, an additive for improving low temperature performance, and an additive for water-based safety.
[0123] The present invention also proposes a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, and a separator between the positive electrode sheet and the negative electrode sheet; the positive electrode sheet and / or the negative electrode sheet is the electrode sheet as described above or the electrode sheet obtained by the preparation method as described above. The electrode sheet proposed by the present invention can be applied not only to the above-mentioned lithium-ion battery, but also to other secondary batteries, including sodium-ion batteries, potassium-ion batteries, etc., without any limitation here.
[0124] In a sixth aspect of the present invention, a use of the above-mentioned lithium-ion battery in an energy storage device, an electrical device or an electronic device is proposed. BRIEF DESCRIPTION OF THE DRAWINGS
[0125] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein: Figure 1 A schematic diagram of the structure of a positive electrode sheet including a water-based safety coating provided by the present invention, wherein 01-positive electrode sheet; 011-active material layer; 022-current collector; 023-water-based safety coating; Figure 2A schematic diagram of the cross-sectional structure of a current collector including a water-based safety coating provided by the present invention along the unwinding direction, wherein 02-positive current collector including a safety coating; 021-reserved slot; 022-current collector; 023-water-based safety coating; 024-non-safety coating area; Figure 3 A top view of a current collector (unstriped) comprising a water-based safety coating provided by the present invention; Figure 4 A schematic diagram of the cross-sectional structure of a current collector including a water-based safety coating provided by the present invention along the unwinding direction, wherein 021 - reserved slot; 022 - current collector; 023 - water-based safety coating. DETAILED DESCRIPTION
[0126] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0127] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0128] In the description of the present invention, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, wherein a and b are real numbers. Unless otherwise specified, each reaction or operation step may be performed in sequence or not. Preferably, the reaction method of the present invention is performed in sequence.
[0129] If no specific techniques or conditions are specified in the following examples, the techniques or conditions described in the literature in the art or the product instructions are used. All reagents or instruments without manufacturer specified are conventional products that can be purchased commercially.
[0130] Example 1 This embodiment provides a lithium ion battery, wherein the positive electrode sheet contains a water-based safety coating, the water-based safety coating contains a binder, a first conductive agent Super P Li and an inorganic filler boehmite, wherein the structural formula of the binder is: .
[0131] (1) Preparation of binder: a) adding 1000 parts by weight of distilled water into a reaction vessel, starting stirring, introducing high-purity nitrogen to deoxygenate for 1 hour, then adding 50 parts by weight of acrylonitrile, 35 parts by weight of lithium acrylate, and 15 parts by weight of methyl acrylate, and heating to 65° C. and maintaining the temperature under an inert atmosphere; b) then adding 5 parts by weight of a 20% ammonium persulfate solution as an initiator to initiate the reaction, and reacting for 5 hours; c) After the reaction is completed, the mixture is filtered, dried, crushed and sieved to obtain a binder. The proportion of -CN in the binder is n 1 50%, -COOLi accounts for n 2 35%, -COOCH 3 Proportion 3 is 15%, weight average molecular weight M w 3.5×10 5 , number average molecular weight M w 1.8×10 5 , M w / M n =1.94, electrolyte absorption rate c=23%.
[0132] (2) Preparation of positive electrode current collector containing water-based safety coating: Deionized water was used as solvent, and 10 parts of the above-mentioned adhesive was added for gluing. The amount of deionized water was adjusted until a solid content of 15% and a viscosity of 2.0×10 4 mPa·s glue; then 88 parts of inorganic filler boehmite (median particle size D v50 The surface area is 0.4 μm and the specific surface area is 9.5 m 2 / g) and 2 parts of the first conductive agent Super P Li are added to the glue solution and mixed evenly to obtain a water-based safety coating slurry with a solid content of 20% and a viscosity of 750 mPa·s. The water-based safety coating slurry is coated on both sides of the aluminum foil by gravure printing. A2 and L B2 are all set to 0, that is, L A1 =L B1 =L A =L B =L,N 1 =N 3 =1,N 2=4. In addition, the oven temperature during printing needs to be set to 95°C and the printing speed to 30 m / min. Finally, a positive electrode current collector with a double-sided bottom coating of a water-based safety coating is obtained. The double-sided coating surface density of the water-based safety coating is 10 mg / 1540.25 mm 2 The double-sided thickness is 5.1 μm, the double-sided membrane resistance is 2.8Ω @0.4T, and the adhesion between the water-based safety coating and the current collector is 1318 N / m.
[0133] (3) Preparation of positive electrode: The positive electrode active material, conductive agent (a mixture of conductive carbon black and carbon nanotubes, mass ratio 6:5), PVDF binder and NMP are mixed evenly at a mass ratio of 97.6:1.1:1.3:35 to form a positive electrode slurry with a solid content of 75% and a viscosity of 7000 mPa·s. The positive electrode slurry is coated on one side of the above-mentioned current collector aluminum foil containing the water-based safety coating, and after drying and rolling at 85°C, the positive electrode slurry is coated and dried on the other side of the current collector aluminum foil containing the water-based safety coating according to the above method, and then the positive electrode sheet coated with the positive electrode active material layer on both sides is cold pressed; then the edges are trimmed and striped to form a lithium-ion battery positive electrode sheet.
[0134] (4) Preparation of negative electrode sheet: Using water as solvent, graphite, thickener and SBR binder were mixed uniformly in a mass ratio of 97.7:1.1:1.2 to prepare a lithium ion battery negative electrode slurry with a solid content of 50% and a viscosity of 5000 mPa·s, which was coated on one side of the current collector copper foil and dried and rolled at 80°C. Then, the negative electrode slurry was coated and dried on the other side of the copper foil according to the above method to obtain a negative electrode sheet coated with active materials on both sides.
[0135] (5) Preparation of electrolyte: Lithium hexafluorophosphate (LiPF 6 ) was dissolved in a mixed solvent of dimethyl carbonate (DMC), ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (the mass ratio of DMC, EC and EMC was 3:5:2) to obtain an electrolyte.
[0136] (6) Preparation of batteries: The prepared positive electrode sheet, negative electrode sheet and separator are wound into a battery cell with a capacity of about 5 Ah. The separator is located between the adjacent positive electrode sheet and negative electrode sheet, the positive electrode is spot welded out with an aluminum tab, and the negative electrode is spot welded out with a nickel tab; the battery cell is then placed in an aluminum-plastic packaging bag, baked, and injected with the above electrolyte, and finally made into a lithium-ion battery through packaging, formation, capacity division and other processes.
[0137] Example 2 The difference from Example 1 is that 35 parts of lithium acrylate in the synthetic binder are replaced with an equal amount of sodium acrylate, and the structural formula of the obtained binder is: .
[0138] The rest is the same as Example 1 and will not be described again here.
[0139] Example 3 The difference from Example 1 is that 15 parts of methyl acrylate in the synthetic binder are replaced with an equal amount of butyl acrylate, and the structural formula of the binder is: .
[0140] The rest is the same as Example 1 and will not be described again here.
[0141] Example 4 The difference from Example 1 is that the proportion of -CN in the binder is n 1 56.7%, -COOR 1 Proportion 2 28.3%, -COOR 2 Proportion 3 Correspondingly, when synthesizing the binder, the weight of acrylonitrile is changed to 56.7 parts, the weight of lithium acrylate is changed to 28.3 parts, and the weight of methyl acrylate is still 15 parts.
[0142] The rest is the same as Example 1 and will not be described again here.
[0143] Example 5 The difference from Example 1 is that the proportion of -CN in the binder is n 1 46.4%, -COOR 1 Proportion 2 38.6%, -COOR 2 Proportion 3 Correspondingly, when synthesizing the binder, the weight of acrylonitrile is changed to 46.4 parts, the weight of lithium acrylate is changed to 38.6 parts, and the weight of methyl acrylate is still 15 parts.
[0144] The rest is the same as Example 1 and will not be described again here.
[0145] Example 6 The difference from Example 1 is that the proportion of -CN in the binder is n 1 56%, -COOR 1 Proportion 2 39.2%, -COOR 2 Proportion 3Accordingly, when synthesizing the binder, the weight of acrylonitrile is changed to 56 parts, the weight of lithium acrylate is changed to 39.2 parts, and the weight of methyl acrylate is changed to 4.8 parts.
[0146] The rest is the same as Example 1 and will not be described again here.
[0147] Example 7 The difference from Example 1 is that the proportion of -CN in the binder is n 1 49.1%, -COOR 1 Proportion 2 34.3%, -COOR 2 Proportion 3 Accordingly, when synthesizing the binder, the weight of acrylonitrile is changed to 49.1 parts, the weight of lithium acrylate is changed to 34.3 parts, and the weight of methyl acrylate is changed to 16.6 parts.
[0148] The rest is the same as Example 1 and will not be described again here.
[0149] Example 8 The difference from Example 1 is that the proportion of -CN in the binder is n 1 55%, -COOR 1 Proportion 2 30%, -COOR 2 Proportion 3 Correspondingly, when synthesizing the binder, the weight of acrylonitrile is changed to 55 parts, the weight of lithium acrylate is changed to 30 parts, and the weight of methyl acrylate is still 15 parts.
[0150] The rest is the same as Example 1 and will not be described again here.
[0151] Example 9 The difference from Example 1 is that the proportion of -CN in the binder is n 1 53%, -COOR 1 Proportion 2 37%, -COOR 2 Proportion 3 Accordingly, when synthesizing the binder, the weight of acrylonitrile is changed to 53 parts, the weight of lithium acrylate is changed to 37 parts, and the weight of methyl acrylate is changed to 10 parts.
[0152] The rest is the same as Example 1 and will not be described again here.
[0153] Example 10 The difference from Example 1 is that the amount of the first conductive agent Super P Li in the water-based safety coating is 3 parts, the amount of the inorganic filler boehmite is 87 parts, and the amount of the binder is 10 parts.
[0154] The rest is the same as Example 1 and will not be described again here.
[0155] Embodiment 11 The difference from Example 1 is that the amount of the first conductive agent Super P Li in the water-based safety coating is 1.5 parts, the amount of the inorganic filler boehmite is 88.5 parts, and the amount of the binder is 10 parts.
[0156] The rest is the same as Example 1 and will not be described again here.
[0157] Example 12 The difference from Example 1 is that the amount of the first conductive agent Super P Li in the water-based safety coating is 2 parts, the amount of the inorganic filler boehmite is 83 parts, and the amount of the binder is 15 parts.
[0158] The rest is the same as Example 1 and will not be described again here.
[0159] Embodiment 13 The difference from Example 1 is that during coating, a ceramic layer is separately provided in the non-aqueous safety coating area of the B surface, i.e., L B2 ≠0, such as Figure 3 As shown, the total length of the current collector containing the water-based safety coating is L, and the length of the water-based safety coating area on the B surface is L B1 , the length of the non-aqueous safety coating area is L B2 , and L B1 >L B2 , L B1 +L B2 =L B =L A1 =L A =L.
[0160] The rest is the same as Example 1 and will not be described again here.
[0161] Comparative Example 1 The difference from Example 1 is that the proportion of -CN in the binder is n 1 60%, -COOR 1 Proportion 2 40%, -COOR 2 Proportion 3 is 0%, (n 1 +n 2 ) / n 3Accordingly, when synthesizing the binder, the weight of acrylonitrile is changed to 60 parts, the weight of lithium acrylate is changed to 40 parts, and methyl acrylate is not contained.
[0162] The rest is the same as Example 1 and will not be described again here.
[0163] Comparative Example 2 The difference from Example 1 is that the proportion of -CN in the binder is n 1 0%, -COOR 1 Proportion 2 70%, -COOR 2 Proportion 3 is 30%, n 1 / n 2 is 0. Accordingly, when synthesizing the binder, the weight of lithium acrylate is changed to 70 parts, the weight of methyl acrylate is changed to 30 parts, and acrylonitrile is not contained.
[0164] The rest is the same as Example 1 and will not be described again here.
[0165] Comparative Example 3 The difference from Example 1 is that the proportion of -CN in the binder is n 1 75%, -COOR 1 Proportion 2 0%, -COOR 2 Proportion 3 is 25%, n 1 / n 2 Accordingly, when synthesizing the binder, the weight of acrylonitrile is changed to 75 parts, the weight of methyl acrylate is changed to 25 parts, and lithium acrylate is not contained.
[0166] Comparative Example 4 The difference from Example 1 is that the proportion of -CN in the binder is n 1 42.5%, -COOR 1 Proportion 2 42.5%, -COOR 2 Proportion 3 Correspondingly, when synthesizing the binder, the weight of acrylonitrile is changed to 42.5 parts, the weight of lithium acrylate is changed to 42.5 parts, and the weight of methyl acrylate is still 15 parts.
[0167] The rest is the same as Example 1 and will not be described again here.
[0168] Comparative Example 5 The difference from Example 1 is that the proportion of -CN in the binder is n 1 65%, -COOR 1 Proportion2 20%, -COOR 2 Proportion 3 Correspondingly, when synthesizing the binder, the weight of acrylonitrile is changed to 65 parts, the weight of lithium acrylate is changed to 20 parts, and the weight of methyl acrylate is still 15 parts.
[0169] The rest is the same as Example 1 and will not be described again here.
[0170] Comparative Example 6 The difference from Example 1 is that the proportion of -CN in the binder is n 1 56.5%, -COOR 1 The proportion is n 2 39.5%, -COOR 2 The proportion is n 3 Accordingly, when synthesizing the binder, the weight of acrylonitrile is changed to 56.5 parts, the weight of lithium acrylate is changed to 39.5 parts, and the weight of methyl acrylate is changed to 4 parts.
[0171] The rest is the same as Example 1 and will not be described again here.
[0172] Comparative Example 7 The difference from Example 1 is that the proportion of -CN in the binder is n 1 29.4%, -COOR 1 The proportion is n 2 20.6%, -COOR 2 The proportion is n 3 Accordingly, when synthesizing the binder, the weight of acrylonitrile is changed to 29.4 parts, the weight of lithium acrylate is changed to 20.6 parts, and the weight of methyl acrylate is changed to 50 parts.
[0173] The rest is the same as Example 1 and will not be described again here.
[0174] Comparative Example 8 The difference from Example 1 is that the weight of the initiator (20% ammonium persulfate solution by mass) is adjusted to 2 parts, so that the weight average molecular weight M of the prepared adhesive is w 5×10 5 , number average molecular weight M w 1×10 5 , M w / M n =5.
[0175] The rest is the same as Example 1 and will not be described again here.
[0176] Comparative Example 9 The difference from Example 1 is that the amount of the first conductive agent in the water-based safety coating is increased to 6.0 parts, the amount of boehmite is reduced to 84 parts, the amount of the binder remains unchanged at 10 parts, and the film resistance is rapidly reduced to 0.3Ω @0.4 T.
[0177] The rest is the same as Example 1 and will not be described again here.
[0178] Comparative Example 10 The difference from Example 1 is that the amount of the first conductive agent in the water-based safety coating is reduced to 0.2 parts, the amount of boehmite is increased to 89.8 parts, the amount of the binder remains unchanged at 10 parts, and the film resistance increases rapidly to 12.1Ω @0.4T.
[0179] The rest is the same as Example 1 and will not be described again here.
[0180] Comparative Example 11 The difference from Example 1 is that the solid content of the prepared water-based safety coating slurry is increased to 28%, and the thickness of the obtained water-based safety coating is increased to 15.9 μm.
[0181] The rest is the same as Example 1 and will not be described again here.
[0182] Comparative Example 12 The difference from Example 1 is that the amount of binder is reduced to 0.53 parts, and the amount of boehmite is increased to 97.47 parts.
[0183] The rest is the same as Example 1 and will not be described again here.
[0184] Comparative Example 13 The difference from Example 1 is that the amount of binder is increased to 25 parts, and the amount of boehmite is reduced to 73 parts.
[0185] The rest is the same as Example 1 and will not be described again here.
[0186] Comparative Example 14 The difference from Example 1 is that the binder is replaced by PVDF binder, and the solvent is replaced by NMP (N-methylpyrrolidone) from deionized water.
[0187] The rest is the same as Example 1 and will not be described again here.
[0188] Comparative Example 15 The difference from Example 1 is that the surface of the positive electrode current collector is not coated with a water-based safety coating.
[0189] The rest is the same as Example 1 and will not be described again here.
[0190] The parameter settings of Examples 1-13 and Comparative Examples 1-15, the solid content, viscosity (in mPa·s) of the obtained water-based safety coating slurry, and the bonding force (in N / m) between the water-based safety coating and the current collector are shown in Table 1 (Example) and Table 2 (Comparative Example): Test method for adhesion of water-based safety coating: Cut the aluminum foil coated with water-based safety coating into rectangular strips with a width of 15mm and a length of 250mm, then cut a piece of transparent tape of the same width and stick it on the non-test surface of the base-coated aluminum foil to prevent the sample from breaking when being torn off. When sticking the transparent tape, try to be smooth to reduce the generation of bubbles and prevent shaking during the test; take a steel plate with a length * width * thickness = 150mm * 50mm * 2mm, and stick double-sided tape on one side of it (the double-sided tape should be kept parallel to the edge of the steel plate and its length is 60mm), and tear off Release paper; align one end of the aforementioned specimen with the exposed double-sided tape, the overlapping length of the specimen and the double-sided tape is the length of the tape, and then use a 2kg pressure wheel to roll back and forth three times on it to complete the preparation of the test sample; conduct an adhesion test on a universal tensile testing machine, place the lower part of the steel plate into the lower test fixture, align the part of the sample that is not adhered to the double-sided tape vertically into the upper test fixture, so that the specimen can be rotated 180° for testing, tighten the fixture, set the test speed to 300mm / min, the test gauge length to 50mm, start the test and read the display.
[0191] Table 1
[0192] Table 2
[0193] Test Case In order to verify the effect of the introduction of the water-based safety coating of the present invention on the performance of the battery cell, the electrolyte absorption rate c of the binder and the double-sided film resistance R of the water-based safety coating, as well as the puncture performance, low-temperature discharge performance, rate performance and cycle performance of the battery cell were tested.
[0194] Electrolyte absorption rate test method: Pour the binder solution into a polytetrafluoroethylene plate, bake it to volatilize the deionized water and obtain an adhesive polymer film. The thickness of the film is controlled at 100μm, and it is cut into a 50mm long × 50mm wide film. After that, the film is vacuum dried for 24 hours and weighed. Then, the completely dried film is immersed in an electrolyte at 80℃ for 12 hours and then taken out. The electrolyte attached to the surface of the film is wiped off and the weight of the film after absorbing the electrolyte is weighed. The increase rate (%) of the weight of the film before and after being immersed in the electrolyte is the 80℃ absorption rate of the binder. o C of electrolyte absorption rate.
[0195] Diaphragm resistance test method: The instrument used for the diaphragm resistance test is the ACCFILM diaphragm resistance test system (model TT-ACCF-G2A) of Hangzhou Chuanyuan Technology Co., Ltd. The pressure during the test is 0.4 t and the pressure holding time is 10 s.
[0196] Needle penetration test method: charge to 4.45 V at 1.0 C constant current and constant voltage at room temperature, with a cut-off rate of 0.05 C, and then subject the fully charged cell to a needle penetration test. During the test, the deep pit side of the cell faces upward, and a steel nail with a diameter of 4.0 mm is used to completely pierce the cell at a speed of 40 mm / s. The nail penetration position is located at the left, middle, and right positions of the largest surface of the cell (5 cells are tested at each position). Keep for 1 hour. The cell passes the test if it does not catch fire or explode.
[0197] Low temperature discharge performance test method: discharge at 1 C constant current to 3 V, leave for 5 min; set the temperature box to 25 ° C and leave for 60 min; charge at 1.0 C constant current and constant voltage to 4.45 V, with a cut-off rate of 0.02 C; leave for 5 min, discharge at 0.2 C constant current to 3 V, and record the capacity when discharged to 3 V at 0.2 C as the initial capacity C 0 ; Set the incubator to 25℃ and leave for 60 min; Charge to 4.45 V at 1.0 C constant current and constant voltage, with a cutoff rate of 0.02 C; Leave for 5 min, set the incubator to -10℃, leave for 120 min, then discharge the cell at 0.2 C to 3.0 V, and record the capacity C when discharged to 3.4 V and 3.0 V 1 and C 2 , C 1 With C 0 The ratio is the capacity retention rate when discharged to 3.4 V at -10°C.
[0198] The rate discharge performance test method is as follows: discharge at 1 C constant current to 3 V and leave for 5 min; charge at 1.0 C constant current and constant voltage to 4.45 V, with a cut-off rate of 0.02 C and leave for 5 min; discharge at 0.2 C constant current to 3 V, and record the capacity when discharged to 3 V at 0.2 C as the initial capacity C 3 ; Charge to 4.45 V at 1.0 C constant current and constant voltage, cut-off rate 0.02 C, and leave for 5 min; then discharge the cell at 0.2 C to 3.0 V, and record the capacity C when discharged to 3.4 V and 3.0 V 4 and C 5 , C 4 With C 3 The ratio is the capacity retention rate when discharged to 3.4 V at 2C.
[0199] Cycling performance test method: Under the condition of ambient temperature of 25±2℃, discharge the battery cell at 0.2 constant current to 3.0V, then charge it to 4.45V at 3C constant current and constant voltage, with a cut-off rate of 0.05C, and record the voltage, internal resistance, capacity and thickness of the battery cell when it is fully charged for the first time (600gPPG is used for thickness measurement). The cycling process is in accordance with the following HFC standard: discharge to 3V at 0.2C constant current; charge to 4.25V at 3.0C constant current; charge to 4.25V at 2.5C constant current; charge to 4.45V at 2.0C constant current; charge to 4.50V at 1.4C constant current and constant voltage, with a cut-off rate of 0.3C; charge to 4.45V at 2A constant current and constant voltage, with a cut-off rate of 0.05C; discharge to 3V at 1.0C constant current. The above steps are considered one cycle. After 49 cycles, low current recovery is performed according to the following system: charge to 4.25 V at 3.0 C constant current; charge to 4.25 V at 2.5 C constant current; charge to 4.45 V at 2.0 C constant current; charge to 4.50 V at 1.4 C constant current and constant voltage, with a cut-off rate of 0.3 C; charge to 4.45 V at 2 A constant current and constant voltage, with a cut-off rate of 0.05 C; discharge to 3 V at 0.2 C constant current; charge to 4.45 V at 3.0 C constant current and constant voltage, with a cut-off rate of 0.05 C. Record the fully charged cell voltage, internal resistance, and thickness (600 gPPG is used for thickness measurement) every 100 cycles.
[0200] The secondary batteries obtained in Examples 1-13 and Comparative Examples 1-15 were tested, and the test results are shown in Table 3 (Examples) and Table 4 (Comparative Examples).
[0201] Table 3
[0202] Table 4
[0203] From the comparison of the test results in the above table, it can be seen that compared with comparative examples 1-15, the water-based safety coating in embodiment 1-13 satisfies 2≤R×d≤50, and 10%≤c≤50%, 5≤(x+z) / y≤20, 1.2≤z / x≤2, and the pass rate of the corresponding battery cell's puncture test is significantly improved from 0% to more than 90%. At the same time, the low-temperature discharge performance, rate discharge performance and cycle performance are also improved, and the performance is comparable to that of the battery cell with an oily primer using a conventional PVDF binder, and the battery cell with a ceramic layer separately arranged in the non-aqueous safety coating area.
[0204] Examples 1-13 and Comparative Examples 1-3 show that cyano, ester and carboxylate groups in the adhesive are all essential groups, and the lack of any one of the groups will lead to deterioration of the performance of the battery cell.
[0205] Examples 1-13 and Comparative Examples 4-8 show that the values of x, y, z in the binder and their relationship, M w / M n The ratios will have an impact on the water-based safety coating, and when they are not within the specified range of the present invention, the performance of the battery cell will deteriorate.
[0206] From Examples 1-13 and Comparative Examples 9-11, it can be seen that the content of the conductive agent and the solid content of the slurry are not set reasonably when preparing the water-based coating slurry, so that R×d is not within the range given by the present invention, which also leads to the deterioration of the battery performance. Comparative Examples 12-13 are because the amount of binder is too low or too high, resulting in poor battery performance.
[0207] In summary, the binder provided by the present invention is characterized by limiting the -CN, -COOR 1 and-COOR 2 The proportion of all groups (-CN accounts for n 1 、-COOR 1 The proportion of all groups is n 2 and-COOR 2 The proportion of all groups is n 3 ), and n 1 、n 2 、n 3 The relative relationship between the two, and at the same time, the electrolyte absorption rate c of the binder at 80°C is limited, as well as the resistance R and thickness d of the double-sided membrane containing the water-based safety coating, so as to achieve the purpose of not deteriorating the safety performance and cycle performance of the battery, and at the same time improving the low-temperature discharge performance and rate discharge performance of the battery. The battery provided by the present invention satisfies 2≤R×d≤50, and 10%≤c≤50%, 5≤(x+z) / y≤20, 1.2≤z / x≤2, and can achieve a needle puncture pass rate of more than 90%, and at the same time, the capacity retention rate after 800 cycles at 25°C is not less than 89%, the discharge capacity at -10°C is not less than 70% @3.4V, and the discharge capacity at 2C is not less than 70% @3.4V.
[0208] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A polyacrylate adhesive, characterized in that: The structural formula of the polyacrylate binder is: ; wherein each occurrence of R1 is independently selected from H, Li or Na; Each occurrence of R2 is independently selected from substituted or unsubstituted C1~C 10 The alkyl group; And 5≤(x+z) / y≤20, 1.2≤z / x≤2, x, y, z are all not 0.
2. The polyacrylate adhesive according to claim 1, characterized in that: The weight average molecular weight M of the polyacrylate binder w The range is 200000~500000, the number average molecular weight M n The range is 100000~400000; The weight average molecular weight M of the polyacrylate binder w and number average molecular weight M n The ratio M w / M n ≤3.
3. The polyacrylate adhesive according to claim 1, characterized in that: The electrolyte absorption rate of the polyacrylate adhesive at 80° C. is 10% to 50%.
4. A water-based safety coating, characterized in that: The raw materials of the water-based safety coating include the polyacrylate binder as described in any one of claims 1 to 3, a first conductive agent and an inorganic filler.
5. The water-based safety coating according to claim 4, characterized in that: The mass percentage of the polyacrylate binder in the water-based safety coating is 1% to 24%.
6. The water-based safety coating according to claim 4, characterized in that: Include at least one of the following: A1) the mass ratio of the first conductive agent, the polyacrylate binder, and the inorganic filler is (0.5-5): (1-24): (71-98.5); A2) the mass percentage of the first conductive agent to the water-based safety coating is 0.5% to 5%; A3) The inorganic filler has a median particle size range of 0.2 to 4 μm and a specific surface area of 5 to 50 m 2 / g; A4) The raw materials of the water-based safety coating further include a heat-stable active substance; A5) When A4) is included, the mass ratio of the first conductive agent, the polyacrylate binder, the inorganic filler, and the thermally stable active substance is (0.5-5): (1-24): (1-97.5): (1-97.5); A6) When A4) is included, the thermally stable active material includes one or both of lithium iron phosphate and lithium manganese iron phosphate.
7. An electrode sheet, characterized in that: include: current collector; active material layer; A water-based safety coating as described in any one of claims 4 to 6.
8. The electrode sheet according to claim 7, characterized in that: The water-based safety coating is coated on at least one side of the current collector, and the active material layer is coated on a side of the water-based safety coating away from the current collector and / or on a side of the current collector away from the water-based safety coating; Alternatively, the active material layer is coated on at least one side of the current collector, and the aqueous safety coating is coated on the side of the active material layer away from the current collector and / or on the side of the current collector away from the active material layer.
9. The electrode sheet according to claim 8, characterized in that: The water-based safety coating is coated on both sides of the current collector; the water-based safety coating satisfies at least one of the following conditions: B1) the double-sided thickness of the water-based safety coating is 1 to 20 μm; B2) The double-sided coating density of the water-based safety coating is 2-35 mg / 1540.25 mm 2 ; B3) The double-sided membrane resistance of the water-based safety coating tested under a pressure of 0.4 t is 0.5~5Ω; B4) The double-sided thickness d of the water-based safety coating and the value of the double-sided membrane resistance R under a pressure of 0.4 t satisfy the condition: 2≤R×d≤50; B5) The distance W between the left edge of the water-based safety coating on the A side of the current collector and the left edge of the current collector along the direction perpendicular to the unwinding direction of the current collector A1 The range is 2mm~30mm, and the distance W between the right edge and the right edge of the current collector is A2 The range is 2mm~30mm; the distance W between the left edge of the water-based safety coating on the B side of the current collector and the left edge of the current collector B1 The range is 3mm~30mm, and the distance W between the right edge and the right edge of the current collector is B2 The range is 3mm~30mm; and W B1 -W A1 ≥1mm, W B2 -W A2 ≥1mm.
10. A method for preparing an electrode sheet according to any one of claims 7 to 9, characterized in that: Includes steps: Mixing the polyacrylate adhesive with water and performing gluing to obtain a glue solution; The first conductive agent and the inorganic filler are mixed evenly with the glue, or the first conductive agent, the thermally stable active substance and the inorganic filler are mixed evenly with the glue to obtain a water-based safety coating slurry; The aqueous safety coating slurry is applied to one or both sides of the current collector, or the surface of the active material layer away from the current collector to obtain the electrode sheet.
11. The method for preparing an electrode sheet according to claim 10, characterized in that: Include at least one of the following: C1) The mass ratio of the first conductive agent, the polyacrylate binder, and the inorganic filler is (0.5-5): (1-24): (71-98.5); C2) the solid content of the glue is 10% to 30%; C3) The viscosity of the glue is 1×10 3 ~3×10 4 mPa·s; C4) The solid content of the water-based safety coating slurry is ≥ 10%; C5) the viscosity of the aqueous safety coating slurry is ≥50 mPa·s; C6) the dyne value of the current collector is ≥30 dyn / cm; C7) applying the aqueous safety coating slurry to one or both sides of the current collector, or the surface of the active material layer away from the current collector, by gravure printing; C8) When C7) is included, the oven temperature during gravure printing is 90-110°C and the printing speed is 10-50 m / min; C9) The mass ratio of the first conductive agent, polyacrylate binder, inorganic filler and thermally stable active substance is (0.5~5):(1~24):(1~97.5):(1~97.5).
12. A lithium ion battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, and a separator between the positive electrode sheet and the negative electrode sheet; the positive electrode sheet and / or the negative electrode sheet is the electrode sheet according to any one of claims 7 to 9 or the electrode sheet obtained by the preparation method according to any one of claims 10 to 11.
13. Use of the lithium-ion battery according to claim 12 in an energy storage device, an electrical device or an electronic device.
Citation Information
Patent Citations
A phosphate Fe, lithium and aluminum shell column battery and its making technology
CN101188310A
Acrylonitrile copolymer adhesive and application thereof in lithium ion batteries
CN106220779A
Positive electrode binder and preparation method thereof, battery positive electrode and lithium battery
CN112500817A
High-temperature-resistant and low-moisture diaphragm binder as well as preparation method and application thereof
CN115404029A
Porous composite foil, positive pole piece, negative pole piece, semi-solid lithium ion battery and preparation method
CN115832195A
